Sieving machine - Myrrha, Marco A. L.; Reifschneider, Francisco J. B. (Pesquisa Agropecuaria Brasileira, 2014)
A low-cost soil sieving machine is presented. It was developed at the "Centro Nacional de Pesquisa de Hortaliças" of EMBRAPA, for use in head houses attached to greenhouse complexes. On average, it takes 50 seconds to sieve 0.054 m3 of soil. Price, as of April/85, is estimated at US 400.